Teachers’ Perception of the Moroccan ICT Portal of the Ministry of Education - El Janous, Youssra; Laafou, Mohamed; El-Hassouny, El Hassan; Madrane, Mourad (European Scientific Journal, ESJ, 2022)
School failure is a difficult experience for students and their families. The identified causes of such failures however vary. While some are related to the educational system, others are extrinsic and related to the family or society. This paper focuses on promoting the notion of equity in education since there is a close relationship between equality of opportunity and the reduction of school failure and drop-out. Oftentimes, students from disadvantaged social backgrounds have less access to teaching aids, which results to the highest rate of school failure. The results interpret two things: the impact of the integration of the ICT in education through the Ministry of National Education and Vocational Training and the use of teaching aids in the performance of students. Through the responses of students and teachers to the questionnaire, two main factors of school failure were distinguished. The first factor is specific to the school such as teaching and evaluation methods, the school climate, the content of the curricula taught, and the difficult relationship between teacher and student, while the second factor is identified outside the school such as the students’ standard of living or the lack of support at home.